Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA): updated treatment recommendations for psoriatic arthritis 2021 - Coates, LC; Soriano, ER; Corp, N; Bertheussen, H; Callis Duffin, K; Campanholo, CB; Chau, J; Eder, L; Fernández-Ávila, DG; FitzGerald, O; Garg, A; Gladman, DD; et al. (Springer Nature, 2022)
Since the second version of the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) treatment recommendations were published in 2015, therapeutic options for psoriatic arthritis (PsA) have advanced considerably. This work reviews the literature since the previous recommendations (data published 2013-2020, including conference presentations between 2017 and 2020) and reports high-quality, evidence-based, domain-focused recommendations for medication selection in PsA developed by GRAPPA clinicians and patient research partners. The overarching principles for the management of adults with PsA were updated by consensus. Principles considering biosimilars and tapering of therapy were added, and the research agenda was revised. Literature searches covered treatments for the key domains of PsA: peripheral arthritis, axial disease, enthesitis, dactylitis, and skin and nail psoriasis; additional searches were performed for PsA-related conditions (uveitis and inflammatory bowel disease) and comorbidities. Individual subcommittees used a GRADE-informed approach, taking into account the quality of evidence for therapies, to generate recommendations for each of these domains, which were incorporated into an overall schema. Choice of therapy for an individual should ideally address all disease domains active in that patient, supporting shared decision-making. As safety issues often affect potential therapeutic choices, additional consideration was given to relevant comorbidities. These GRAPPA treatment recommendations provide up-to-date, evidence-based guidance on PsA management for clinicians and people with PsA.